Food and beverage management - Davis, Bernard; Lockwood, Andrew; Alcott, Peter; Pantelidis, Ioannis S. (London Routledge, 2018)
This introductory textbook provides a thorough guide to the management of food and beverage outlets. It is illustrated in full colour and contains in-chapter activities as well as end-of-chapter summaries and revision questions to test the readers' knowledge as they progress.
Chapter 1. Introducing food and beverage management -- Chapter 2. Classifying food and drink service operations -- Chapter 3. Restaurants and events - the direct market -- Chapter 4. Contract foodservice, travel and public sector catering - the indirect market -- Chapter 5. Developing the concept -- Chapter 6. The Menu -- Chapter 7. Purchasing and storage -- Chapter 8. Production and Service -- Chapter 9. Controlling the Operation -- Chapter 10. Staffing Issues -- Chapter 11. Food and beverage marketing -- Chapter 12. Managing quality in food and drink service operations -- Chapter 13. Trends and Developments.
Includes bibliographical references and index.
Keywords: Food service management; Hospitality industry -- Management